Metabolic and motor activity effects of microalgae (Chlorella vulgaris) in laboratory mice - E. L. Zavjalov; D. V. Petrovskii; G. V. Kontsevaya; V. V. Mak; I. P. Uvarov; Y. L. Zav’yalova; O. A. Rozhkov (Вавиловский журнал генетики и селекции, 2017)
In recent years, the microalgae (Chlorella vulgaris) have increasingly attracted great interest as a potential source of pharmacologically active compounds. Showing anticoagulation, antioxidant and antitumor activities of Chlorella revealed its hypotensive properties. The aim of this study was to evaluate the effects of Chlorella suspension on the weight of the animals, their moving activity, and erythropoiesis. The study was performed on males and females of ICR mice. The animals from the experimental group drank only the Chlorella suspension during 3 weeks and were given standard food. Control animals drank during this period only water and had the same food. The body weight of males in the control and the experimental group with Chlorella did not change, while females in the experimental group showed an increase of body weight in a week. A similar pattern was obtained for estimation of animal body weight changes relative to food consumption. The number of red blood cells in females and males from group with Chlorella increased only after 3 weeks after the start of the experiment. Hemoglobin also increased only after 3 weeks after the start of Chlorella consumption, but only for females. All groups of animals had the same motor activity during experiment. Blood sampling resulted in a reduction of activity in control males and females as well as in males with Chlorella. The motor activity of females with Chlorella after blood sampling did not change. So, consumption of the Chlorella suspension by females leads to more effective digestion and resulted in increased body weight, improved erythropoiesis resulted in increased red blood cells and hemoglobin and also increased their resistance to acute stress. The males in the same situation increased only the erythropoiesis.